Preparing Successors for Leadership Another Kind of Hero - Aronoff, C. (A Family Business Publication, 2011)
The founders of the family business must impart their vision and leadership to succeeding generations. Preparing those generations for leadership is challenging and encompasses a lifetime. Aronoff and Ward's strategy for a smooth transition prepares successors for their role in the future of the firm.